2013
DOI: 10.1111/tid.12087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of pre‐transplant desensitization utilizing a plasmapheresis and low‐dose intravenous immunoglobulin protocol on BK viremia in renal transplant recipients

Abstract: This analysis reveals that pre-transplant desensitization significantly increases the risk for BKV viremia and nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…(ii) treatment protocols; (iii) treatment endpoints; (iv) antibody evaluation; (v) crossmatch procedures; (vi) assessment of graft function; (vii) donor type (living or deceased); (viii) DSA strength pretreatment and at transplant; (ix) length of follow-up; and (x) additional risk factors such as repeated mismatches. Tables 1 and 2 give AMR rates and graft survival data, respectively, for selected studies representing variations of the high dose IVIG and PP/low dose IVIG protocols (35,39,40,65,71,75,(81)(82)(83)(84)(85)(86). Because of the variability noted above, these data cannot be taken as a meaningful comparison of the different protocols but, rather, show that despite the increased risk of AMR, good graft and patient survival can be achieved.…”
Section: Desensitization For Hla Antibodymentioning
confidence: 99%
“…(ii) treatment protocols; (iii) treatment endpoints; (iv) antibody evaluation; (v) crossmatch procedures; (vi) assessment of graft function; (vii) donor type (living or deceased); (viii) DSA strength pretreatment and at transplant; (ix) length of follow-up; and (x) additional risk factors such as repeated mismatches. Tables 1 and 2 give AMR rates and graft survival data, respectively, for selected studies representing variations of the high dose IVIG and PP/low dose IVIG protocols (35,39,40,65,71,75,(81)(82)(83)(84)(85)(86). Because of the variability noted above, these data cannot be taken as a meaningful comparison of the different protocols but, rather, show that despite the increased risk of AMR, good graft and patient survival can be achieved.…”
Section: Desensitization For Hla Antibodymentioning
confidence: 99%
“…5,12 Recently pretransplant desensitization with PEx/IVIg has shown to increase the risk for BKV viremia and nephropathy. 13 Recipient risk factors including older age, male sex and donor related risk factors including female sex, active BKV and cytomegalovirus infection and deceased donor transplant are also thought to influence BKV infection. 5,12 In our study all recipients were on tacrolimus-mycophenolate based immunosuppression, a large proportion were elderly males who had received deceased donor transplants, and had additional immunosuppression either in the form of Previous studies have reported that most (95%) BKVN occurs in the first 2 years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Biopsy proven "definite" PVN has an incidence of 5-6%, with a higher incidence in ABO-incompatible donors and following desensitization in highly sensitized recipients. [14][15][16] The Banff Working Group on Polyomavirus Nephropathy recently published a morphologic classification of definite PVN into three groups, Class I, II, and III, based on polyomavirus load and Banff ci score (interstitial fibrosis) for ease of diagnostic communication and comparative data analysis. 17 However, this was a retrospective observational analysis which has not been validated in a mixed population.…”
Section: Prevalencementioning
confidence: 99%
“…6,14,41,42 Recipient factors include old age, male sex, desensitization, and prior kidney transplant with PVN. 16,43…”
Section: Management Strategies Risk Factorsmentioning
confidence: 99%